2016
DOI: 10.1016/j.jcma.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Maternal antineuronal antibodies and risk of childhood autism spectrum disorders: A case–control study

Abstract: Some maternal antineuronal antibodies may contribute significantly to the risk of childhood autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
6
1
Order By: Relevance
“…In the literature, a recent study by Naael et al on the mothers of children with autism found that they had significantly higher levels of anti-Yo and anti-Amphiphysin antibodies than the control group. Anti-Hu and anti-Ri antibodies were also found at higher levels in the mothers of children with autism, but the difference with control groups was not statistically significant [14]. In our study, no significant difference was found between the ASD and control groups in terms of anti-Yo and anti-Amphiphysin values.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…In the literature, a recent study by Naael et al on the mothers of children with autism found that they had significantly higher levels of anti-Yo and anti-Amphiphysin antibodies than the control group. Anti-Hu and anti-Ri antibodies were also found at higher levels in the mothers of children with autism, but the difference with control groups was not statistically significant [14]. In our study, no significant difference was found between the ASD and control groups in terms of anti-Yo and anti-Amphiphysin values.…”
Section: Discussioncontrasting
confidence: 82%
“…In a study by Naael et al on the mothers of children with ASD, anti-Yo and anti-Amphiphysin antibodies were found to be significantly higher than in mothers in the healthy control group. As to anti-Hu and anti-Ri antibodies, they were found at higher rates in the mothers of children with autism than control groups, but the difference was not statistically significant [14].…”
Section: Introductionmentioning
confidence: 71%
“…Several auto-Abs more commonly associated with paraneoplastic syndromes have also been associated with maternal Ab-mediated ASD. In a study using western blot to assess postnatal maternal serum, mothers of a child with ASD were significantly more likely to harbor anti-Yo Abs (with an odds ratio of 2.6) and anti-amphiphysin Abs (odds ratio: 2.5) than were healthy mothers with a typically developed child [ 76 ]. A later study, using ELISA, confirmed the association between maternal anti-amphiphysin Abs and ASD, and found a significant association between anti-Ri Abs and ASD [ 77 ].…”
Section: Clinical Data: Maternal Brain-reactive Abs and Asdmentioning
confidence: 99%
“…Maternal antibodies or other serum factors could cause neurodevelopmental disorders . A case–control study with serum samples of 49 mothers of ASD‐affected children and 73 controls found a higher maternal seropositivity for anti‐Yo antibodies (34.7% vs 13.7%; aOR, 2.60) and anti‐amphiphysin antibodies (40.8% vs 17.8%; aOR, 2.54) in the ASD group . There have been speculations about the development of ASD in children of mothers who received an influenza vaccination in their first trimester of pregnancy.…”
Section: Parental Risk Factorsmentioning
confidence: 99%
“…33 A case-control study with serum samples of 49 mothers of ASD-affected children and 73 controls found a higher maternal seropositivity for anti-Yo antibodies (34.7% vs 13.7%; aOR, 2.60) and anti-amphiphysin antibodies (40.8% vs 17.8%; aOR, 2.54) in the ASD group. 34 There have been speculations about the development of ASD in children of mothers who received an influenza vaccination in their first trimester of pregnancy. However, among a cohort of 196 929 children, of whom 3103 had ASD, no significant association between maternal influenza infection and risk of autism (adjusted hazard ratio: 1.20; 95%CI, 1.04-1.39) was found.…”
Section: Immune Factorsmentioning
confidence: 99%